INTEGRASI NILAI ISLAM DALAM METODE PEMBELAJARAN KELAS VII SMP-IT DAARUL RAHMAN - Abdurrahman Abdurrahman; Lulu Habibah; Nur Azizah; Sholiha Sholiha; Vania Rahma; Hendrayadi Hendrayadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The integration of Islamic values ​​in learning at the junior high school level is very strategic for shaping the religious and social character of students while improving the quality of cognitive, affective, and psychomotor learning outcomes. This study aims to describe the form of integration of Islamic values ​​in the learning method of grade VII at SMP-IT Daarul Rahman, analyze supporting and inhibiting factors, and analyze teacher and student responses to its implementation. The study used a qualitative approach with a field research type (field research) and descriptive plan, with subjects being general subject teachers and Islamic Religious Education (PAI) and grade VII students. Data were collected through learning observations, in-depth interviews, and documentation studies of learning tools, then analyzed through interactive data reduction, presentation, and conclusions. The results of the study indicate that the integration of Islamic values ​​is carried out through planning (lessons learned and school programs based on monotheism), learning implementation (religious motivation, teacher role models, daily worship habits, linking general material with verses of the Qur'an and hadith), and assessment of religious attitudes and characters. The main supporting factors include Islamic school culture, parental support, teacher religious competence, and student enthusiasm; Inhibiting factors include limited class time, heterogeneity in student backgrounds, and teachers' unequal understanding of integrated learning design.